Vegetation sampling of Lesser Prairie Chicken Habitat, Comanche National Grassland - Kuhn, Bernadette, author; Decker, Karin, author; Rondeau, Renée Jane, author; Grunau, Lee, author; Colorado Natural Heritage Program, publisher (Colorado State University. Libraries, 2012)
Colorado Natural Heritage Program ecologists and USFS personnel conducted vegetation sampling at the Comanche National Grassland in 2012 in order to assess vegetation on potential Lesser Prairie Chicken (LEPC) habitat. The study was intended to contrast differences between the inside and the outside of long-term cattle-grazing exclosures, and to determine the overall suitability of LEPC habitat in the vicinity of these exclosures. LEPC habitat treated by disk-plowing in recent (2009) exclosures was also evaluated for the effects of this treatment on habitat suitability for LEPC.
Prerpared for: U.S. Forest Service.
February 2013.
Keywords: Federal Endangered Species Act; effect of habitat modification; LEPC habitat; livestock exclosures; Lesser prairie chicken; Tympanuchus pallidicinctus